Análise das interações proteína-proteína da chaperona de cobre ATX1 em Paracoccidioides brasiliensis - Lugo, Danize Eukales Menezes (2022)
Paracoccidioidomycosis is the most prevalent systemic mycosis in the Americas, mainly in Brazil, Colombia, Venezuela and Argentina. The disease is caused by fungi of the genus Paracoccidiodes that exhibit thermodimorphism. The fungus is present in the soil in the mycelial form at 28°C and in the yeast form in the host at 37°C. The ability to differentiate is considered a virulence factor of this pathogen. Copper (Cu) is an essential component of enzymes that carry out electron transfer reactions. Homeostasis of this metal was first described in Saccharomyces cerevisiae and homologous genes were identified in several organisms. Among these, the ATX1 gene, related to a copper metallochaperone, stands out, which transports Cu1+ from Ctr1 (transmembrane transporter) to Ccc2 (P-type ATPase) in a trans-Golgi vesicle for eventual insertion into Fet3. The latter is a highaffinity Cu-dependent iron absorption protein. Atx1 was identified in S. cerevisiae as a small 8 kDa Cu chaperone, being classified as an antioxidant molecule. Little is known about Cu homeostasis metabolism and the specific function of the ATX1 gene in Paracoccidioides brasiliensis. Thus, the identification of Atx1 interaction networks in P. brasiliensis can elucidate details of Cu metabolism in this organism. The main objective of this research was to characterize, through molecular anchoring, how ATX1 interacts with P. brasiliensis proteins, providing an understanding of the biology of the fungus and aiming to identify possible therapeutic targets as a future perspective. A group of proteins that interact with Atx1 was identified and validated through pull-down assays. These proteins are part of the maintenance of homeostasis, interacting with other proteins of copper metabolism, electron transport and detoxification proteins. These interactions indicate the importance of Atx1 for maintaining copper homeostasis in the fungus, being a potential target for alternative drugs, which may collaborate to expand therapeutic options.